Persistence and Progression of Masked Hypertension: A 5-Year Prospective Study - Xavier Trudel; Alain Milot; Chantal Brisson (International Journal of Hypertension)
Objectives. To examine masked hypertension persistence over 5 years. Methods. White-collar workers were recruited from three public organizations. Blood pressure (BP) was measured using Spacelabs 90207. Manually operated BP was defined as the mean of the first three readings taken at rest. Ambulatory BP was defined as the mean of the next readings taken every 15 minutes and recorded during working hours. BP was assessed three times over 5 years. Masked hypertension was defined as manually operated BP less than 140 and less than 90 mmHg and ambulatory BP at least 135 or at least 85 mmHg. Sustained hypertension was defined as manually operated BP at least 140 or at least 90 mmHg and ambulatory BP at least 135 or at least 85 mmHg or being treated for hypertension. Results. BP measurements were obtained from 1669 participants from whom 232 had masked hypertension at baseline. Persistence of masked hypertension was 38% and 18.5%, after 3 and 5 years, respectively. Progression to sustained hypertension was 26% and 37%, after 3 and 5 years, respectively. Conclusion. Among baseline masked hypertensives, one-third progressed to sustained hypertension and about one out of five remained masked after 5 years, potentially delaying diagnosis and treatment.